Diversity, foraging behaviour of floral visitors and pollination ecology of fennel (Foeniculum vulgare Mill.) - Chaudhary, O P (Journal of Spices and Aromatic Crops, 2006)
A study on floral visitors of fennel (Foeniculum vulgare) conducted at Karnal (Haryana) indi-cated that 39 species visited the crop among which, hymenopterans (47.1%) and dipterans(50.3%) were the most prominent groups. Six Apoidea species contributed 39.5% of the totalvisitors and Italian honeybee, Apis mellifera was the most prominent species (32.5%). Amongthe dipteran species, Episyrphus balteatus was the most prominent species (24.7%). A. melliferawas most abundant with 15.7 bees m-2 observation interval-1 followed by E. balteatus (11.9bees m-2 observation interval-1). All the Apis species started foraging late (09.00 h) and A.mellifera had longer foraging period (spread up to 18.00 h), whereas, A. cerana foraged up to16.00 h and A. dorsata till 14.00 h. Peak activity of dipterans and other hymenopterans wasduring morning and late afternoon hours. Bee-Q application increased Apoidea populationby 29.1%, other hymenopterans by 12.6% and had no effect on dipteran population (3.0%).Mean seed yield of fennel in caged plots was 5.2 g plant-1 compared to 29.7 g plant-1 in openpollinated and 26.6 g plant-1 in bee pollinated crop (an increase of 474.7% and 413.5%, re-spectively). Bee-Q treated plots gave the highest yield of 33.8 g plant-1 (increase of 553.4%).Yields in bee pollination were at par with open pollination signifying the role of insectpollinators other than honeybees, especially dipterans like E. balteatus, Eristalis arvorum¸Eristalis sp. and Musca sp.